Looking down - Fyfield, Frances (London : Time Warner Books, 2005)
In this novel, Sarah Fortune, lawyer and professional mistress, returns in this mystery which is as much about the identity of the human spirit as it is about the unexplained death of an unknown girl.
Keywords: Women lawyers -- Great Britain -- Fiction; Suicide victims -- Fiction; Detective and mystery fiction